2003
DOI: 10.1007/s10350-004-6809-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microscopic Extranodal Tumor Deposits on the Outcome of Patients With Rectal Cancer

Abstract: These data suggest that extranodal deposit is a distinct form of metastatic disease in patients with rectal cancer. The association with vascular invasion and earlier development of metastases probably infers that a significant proportion of extranodal deposits may represent blood-borne spread. These tumor foci should be considered as indicators of poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 16 publications
1
47
2
2
Order By: Relevance
“…The CRM status, i.e., positive or negative, has repeatedly been demonstrated to be the best predictor for local recurrence and disease-free survival (DFS) after preoperative RCT and surgery, and one would expect that a considerable decrease in tumor burden would be associated with a larger CRM [16][17][18]. Although the association of TD with unfavorable prognosis has been confirmed in many colorectal cancer studies, none of them looked at the prognostic value of TD after preoperative RCT [19][20][21][22][23]. Nagtegaal and Quirke [24] and Quirke et al [25] regarded the presence of residual "microfoci" or tumor deposits as a good response to preoperative RCT; they speculated that the presence of TDs in this setting might have resulted from fragmentation of the advanced primary tumor (cT≥3), creating separate tumor nodules of various sizes and shapes in the mesorectum.…”
Section: Introductionmentioning
confidence: 99%
“…The CRM status, i.e., positive or negative, has repeatedly been demonstrated to be the best predictor for local recurrence and disease-free survival (DFS) after preoperative RCT and surgery, and one would expect that a considerable decrease in tumor burden would be associated with a larger CRM [16][17][18]. Although the association of TD with unfavorable prognosis has been confirmed in many colorectal cancer studies, none of them looked at the prognostic value of TD after preoperative RCT [19][20][21][22][23]. Nagtegaal and Quirke [24] and Quirke et al [25] regarded the presence of residual "microfoci" or tumor deposits as a good response to preoperative RCT; they speculated that the presence of TDs in this setting might have resulted from fragmentation of the advanced primary tumor (cT≥3), creating separate tumor nodules of various sizes and shapes in the mesorectum.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, it has been suggested that those nodules often are not derived from destroyed metastatic nodes but are intravascular, perivascular, or perineural extensions of the primary tumor, and represent a feature of poor prognosis, independently of their number and size. 25,50,51 Thus, the sixth edition of the UICC/AJCC staging guidelines classified those nodules into two entities: a nodule with a smooth contour is classified in the pN category as a regional lymph node metastasis, whereas a nodule with an irregular contour is classified in the T category coded as V1 or V2 for venous invasion. 5,6 In the present study, the authors identified tumor nodules without histologic evidence of residual node in 17 cases (11 percent) from Stage III patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some TDs may be lymph node metastases, in which the pre-existing node is no longer recognizable. Strong correlations have been demonstrated between the presence or number of TDs and intramural vascular invasion, extramural vascular invasion, perineural invasion, lymphatic invasion and lymph node metastases (11). Ueno et al demonstrated that the incidence of TDs is higher in cases with extracapsular growth of lymph node metastases, compared with cases with lymph node metastases with an intact capsule (12).…”
Section: Discussionmentioning
confidence: 99%